Triadic parent-child play and toddlers' socio-emotional development: The role of coparenting dynamics - Nandy, Angana (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2021)
Drawing on the family systems perspectives (Minuchin, 1985; 1988) this thesis aimed to make unique contributions to the field of developmental psychology by examining the role of the coparenting relationship in toddlers social and emotional development. Given that family processes do not occur in isolation, examining families as an organized whole is important for strengthening our understanding of the developing child. The current research used observational methods for examining naturalistic parent-toddler interactions during play activities in dyadic (one parent and child) and triadic (both parents and child) contexts. Parent-child play has consistently emerged as a key behaviour that facilitates toddlers emerging socio-emotional competencies. However, there is little understanding of the role of the interactional context in mothers and fathers play behaviours and more importantly the role of observed coparenting in triadic interactions. This thesis, therefore, aimed to (i) advance understanding of the coparenting construct and (ii) illustrate the importance of family-level interactions for toddlers socio-emotional development through an extensive literature review and a series of empirical investigations. Chapter 1 discusses the defining properties, models, measurement methods and factors associated with coparenting dynamics that also determine its stability over time. Chapter 2, at first, highlights the importance of focusing on the developmental period of toddlerhood. Following this, the chapter discusses the important role of parents in parent-toddler play and exemplified the need to adopt a systemic approach for examining parental play behaviours in relation to toddlers socio-emotional development. Chapter 3 outlines the methodology of the empirical studies in detail. In Chapter 4, the empirical studies are presented. Study 1 examined the role of child and parent characteristics, couple s dyadic adjustment and parental functioning in coparenting dynamics. Findings indicated that (i) less supportive coparenting dynamics were evident in families with older parents and (ii) more supportive coparenting dynamics in families were evident in families where fathers reported a higher parental sense of competence. Given that the child is the focus of the coparenting relationship, Study 2 examined the role of toddler temperament in the stability of coparenting dynamics from toddlerhood to the preschool years. Results showed that supportive coparenting remained stable when toddlers were reported as having less difficult and more positive temperamental traits. Study 3 (part 1) examined contextual and parent gender based variations in parents play behaviours. Results showed that both parents engaged in significantly less toy play (toy touch/manipulation) and verbal facilitation (using only language to guide play) in the triadic context in comparison with the dyadic context. Additionally, Study 3 (part 2) showed that maternal toy play was significantly positively associated with toddlers socio-emotional development but only when this was embedded in a supportive coparenting context. Study 4 (part 1) examined contextual and parent gender based variations in the communicative functions of parents child-directed speech (CDS). Results showed that both parents used significantly more facilitative speech (questions) in the triadic context and provided more gentle guidance (praise and encouragement) in the dyadic context. Fathers used more directives commands and prohibitions) than mothers but parents referential CDS (labelling and describing speech) was not affected by either context or parental gender. Furthermore, Study 4 (part 2) showed that coparenting did not play a significant role in these communicative functions of parental CDS. Results from this study also showed positive associations between higher verbosity in toddlers whose mothers asked more questions in the triadic context. Study 5 examined direct associations between coparenting dynamics and toddlers adaptive functioning and results showed that toddlers were reported as having poorer adaptive functioning in families with higher levels of coparenting undermining. Chapter 5 discusses the implications of the findings, strengths and limitations of the study and directions for future research. In summary, this thesis advances understanding of the coparenting construct and the role of coparenting dynamics in triadic-level family interactions and toddlers socio-emotional development.
APPROVED
Keywords: Toddlers; Socio-emotional development; parent-child play; Coparenting